INNOVATIVE STRATEGIES AS A DECISIVE FACTOR IN BUSINESS DEVELOPMENT IN RURAL AREAS - Матієнко, Василь М. (Journal of Strategic Economic Research, 2023)
The article presents the results of research on the role of forming an innovative strategy for business development in rural areas. It has been proven that in the conditions of a turbulent economic environment, which is characterized by the rapid development of information technologies, the full-scale war of the Russian Federation, the consequences of the pandemic, and increased competition, it is extremely important for the development of business in rural areas to conduct effective innovative management of enterprises. The article substantiates at the theoretical level the vector component of innovative business management, namely the innovative strategy of business in rural areas. It has been proven that this specific direction of business development is aimed at strengthening the position of rural areas, achieving the intended goals, meeting the needs of customers as efficiently as possible through the use of innovative management methods and technologies. In the context of innovative management, it is determined that the development of business in rural areas involves constant changes and flexible adaptation to these changes, an approach to identifying innovative strategies based on a change in the current state of one or more management objects is formed: the market, the state of business, the industry aspect, the presence innovative technologies, reference strategies that are important for rural areas are singled out, namely, concentrated growth, integrated growth, diversified growth, and planned reduction. The justification for choosing an innovative business strategy should take into account the fact of compliance with the general strategy for the development of rural areas, as well as the possibility of market acceptance of a new product and the corresponding risks of promoting this product in the future. The key factor in choosing a particular innovation strategy is the existing innovation potential of the business.